2017
DOI: 10.2139/ssrn.2987367
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of Abortion and Contraception Policies on Young Women's Reproductive Choices, Schooling and Labor Supply

Abstract: In this paper, I evaluate the effects of regulations that limit the availability of abortion services, as well as the impact of policies that subsidize contraception, on abortion and contraceptive choices of young women and on their life-cycle fertility, schooling and labor supply. I specify and structurally estimate a dynamic life-cycle model of abortion, contraceptive use, schooling and labor supply decisions using data from the NLSY97 combined with aggregate abortion provider data from the Guttmacher Instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Studies at the national level assessed a comparatively wider range of regulations: one19 used data from NARAL (a reproductive rights advocacy group) to group state-level TRAP laws into two categories (licensing fees, plant/personnel laws), and another20 used the same source but grouped TRAP laws according to a six-category classification scheme. The remaining study21 assessed the impact of supply-side regulations indirectly by simulating the effect of TRAP-driven provider closures on the national scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies at the national level assessed a comparatively wider range of regulations: one19 used data from NARAL (a reproductive rights advocacy group) to group state-level TRAP laws into two categories (licensing fees, plant/personnel laws), and another20 used the same source but grouped TRAP laws according to a six-category classification scheme. The remaining study21 assessed the impact of supply-side regulations indirectly by simulating the effect of TRAP-driven provider closures on the national scale.…”
Section: Resultsmentioning
confidence: 99%
“…Three of the five articles that assessed abortion outcomes reported an inverse association between certain TRAP laws and abortion rates, with exposure linked to a decrease in abortion 5 18 21. Depending on the analysis, the magnitude of this effect ranged from a 6.8% decline in the abortion rate among women aged 18–30 years,21 to a 13% decline in the abortion rate among all women of childbearing age (15–44 years),5 to a 72% decrease in the abortion rate among women presenting at or after 16 weeks’ gestation 18. In contrast, one study in this subgroup found no effect of TRAP laws on abortion demand,19 and one reported a potential increase in abortions following TRAP legislation 20.…”
Section: Resultsmentioning
confidence: 99%
“…For example, women from rural areas could need to travel long distances to reach providers, women with low incomes could lack access to necessary transportation and financial resources, and single parents or caregivers could struggle to find time for repeated visits to facilities because of family obligations and lack of alternative caregivers. Meanwhile, for women or adolescents at risk of domestic violence, the necessity of multiple visits to health facilities could create safety concerns …”
Section: Undermining International Human Rights Standards and Public mentioning
confidence: 99%
“…Meanwhile, for women or adolescents at risk of domestic violence, the necessity of multiple visits to health facilities could create safety concerns. 27,28 Impositions of mandatory waiting periods also undermine women's agency and ability to make autonomous decisions about their bodies and their lives. These impositions imply that without the required "reflection period," women would make rash decisions or would not properly consider the impact of their decisions.…”
Section: Undermining International Human Rights Standards and Publimentioning
confidence: 99%
“…Imperfect contraceptive control in dynamic models of life cycle fertility behavior goes back to at least Heckman and Willis (1976). Since then, a growing number of papers have estimated dynamic economic models including imperfect contraceptive control in relation to contraceptive choices (Carro & Mira, 2006), female labor supply (Adda, Dustmann, & Stevens, 2017; Amador, 2017; Hotz & Miller, 1988; Sheran, 2007), habit persistence in teen sex and the effectiveness of contraceptive policies (Arcidiacono, Khwaja, & Ouyang, 2012) and the fertility risk and abortion use over the life cycle (Choi, 2017).…”
Section: Introductionmentioning
confidence: 99%